Studies on Dynamic Thermogravimetry of Barium salts of a-Amino Substituted Fatty Acids - Varma, R.P.; Goel, Harmendra; Malhotra, V.K. (Asian Journal of Chemistry, 2010)
The thermal decompositions of barium salts of α-amino substituted fatty acids (n-butyric acid, n-caproic acid and iso-caproic acid) was studied by thermogravimetry (TG) under dynamic conditions. Energies of activation have been evaluated by mechanistic models and Coats and Redfern equation. The order of reaction is found to be zero. The values of frequency factor Z, entropy ΔS and free energy ΔG of activation have been evaluated and a probable mechanism of decomposition has been proposed.